A Study of Depok City Morphology in a Century - Ari Widyati Purwantiasning; Saeful Bahri (International Journal of Built Environment and Scientific Research, 2024)
This paper examines the morphological changes of Depok City in one century (1920- 2020) by using a morphological component approach of land use, road patterns, and building patterns. This study used the historical method, which includes four stages: heuristics, criticism, interpretation, and historiography. The results showed that the morphological growth of Depok City showed significant growth and changes. The land use of Depok City in the last century has shown changes with an increase in the residential, trade, and service sectors, and industry, on the other hand, a reduction in the agricultural and plantation sectors. The street pattern network of Depok City shows a change from a linear pattern to a spinal pattern and currently has a mixed pattern. The building pattern that was previously linear then spread to cover almost the entire Depok area. The residential, religious, and colonial-style agricultural products storage buildings are now developing into modern-style residential.